2019
DOI: 10.1155/2019/1018034
|View full text |Cite
|
Sign up to set email alerts
|

Research Progress of the Functional Role of ACK1 in Breast Cancer

Abstract: ACK1 is a nonreceptor tyrosine kinase with a unique structure, which is tightly related to the biological behavior of tumors. Previous studies have demonstrated that ACK1 was involved with multiple signaling pathways of tumor progression. Its crucial role in tumor cell proliferation, apoptosis, invasion, and metastasis was tightly related to the prognosis and clinicopathology of cancer. ACK1 has a unique way of regulating cellular pathways, different from other nonreceptor tyrosine kinases. As an oncogenic kin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 60 publications
(94 reference statements)
0
18
0
Order By: Relevance
“…57 ACK1 has been shown to be a tumor initiator and involved with tumor progression. 58 Similarly, Wu et al…”
Section: Lncrnas In Radiation Responsementioning
confidence: 92%
“…57 ACK1 has been shown to be a tumor initiator and involved with tumor progression. 58 Similarly, Wu et al…”
Section: Lncrnas In Radiation Responsementioning
confidence: 92%
“…Role of Activated Cdc42-Associated Kinase 1 (ACK1/TNK2)-Inhibitors in Precision Oncology DOI: http://dx.doi.org/10.5772/intechopen.102343 severity progression and negatively correlated to the survival rate in breast cancer patients. [4,12,[26][27][28][29][30] However clinical trials of targeting ACK1 in triple negative breast cancers (TNBCs) have not shown any promising results with specific inhibitors. Many tyrosine kinases (EGFR), oncoproteins (AKT), tumor suppressor proteins (Wwox), and epigenetic modification regulatory proteins (KDM3A) interacts with ACK1 in breast cancer [4,[28][29][30][31][32].…”
Section: Representation Of Various Exogenous and Endogenous Agents Ac...mentioning
confidence: 99%
“…As the inhibitors are developed by only limited methods (screening small molecules and fragment libraries), it have weak affinities which makes the selection of drug candidates difficult and time consuming. Further the development of allosteric inhibitors of ACK1 is also difficult as 1), ( 2), ( 3), ( 4), KRCA-0008 ( 5), (R)-9b ( 6), XMD8-87 (7), XMD16-5 (8), benzopyrimidodiaze-pinone derivatives (( 9), ( 10)). Adapted from Aoxue Wang et al [6].…”
Section: Challengesmentioning
confidence: 99%
See 2 more Smart Citations